2022
DOI: 10.3389/fendo.2022.837731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perinatal Outcomes of Letrozole-Induced Ovulation and Hormone Replacement Therapy Protocols in Patients With Abnormal Ovulation Undergoing Frozen-Thawed Embryo Transfer: A Propensity Score Matching Analysis

Abstract: BackgroundWith the increasing use of frozen embryo transfer (FET), the best endometrial preparation protocol is continuously being discussed. The hormone replacement therapy (HRT) cycle and letrozole-induced ovulation (L-OI) cycle are available protocols for patients with abnormal ovulation. Previous comparisons of the two protocols have focused on pregnancy outcomes, with less attention to perinatal outcomes, and population heterogeneity was large; thus, convincing conclusions about which protocol is more app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…The largest study used propensity score matching (PSM) with 1461 women in both the letrozole ± hMG and HRT FET group and reported similar LBR in crude as well as in adjusted analysis [aOR 0.95 (95% CI 0.81–1.12)] [7]. Both Day 3 embryo and blastocyst transfers as well as single and double embryo transfers were included, but neither type nor number of embryos transferred were included in the PSM [7]. In the most recent paper from the centre, only single blastocyst transfers were included with 502 in the letrozole ± hMG group and 2280 in the HRT FET group with a significantly higher LBR (aOR 1.30 (95% CI 1.06–1.58)) and a lower MR [aOR 0.63 (95% CI 0.44–0.90)] in letrozole ± hMG compared to HRT FET [11].…”
Section: Letrozole ∗Frozen-thawed Embryo Transfer Compared To Hormone...mentioning
confidence: 99%
See 3 more Smart Citations
“…The largest study used propensity score matching (PSM) with 1461 women in both the letrozole ± hMG and HRT FET group and reported similar LBR in crude as well as in adjusted analysis [aOR 0.95 (95% CI 0.81–1.12)] [7]. Both Day 3 embryo and blastocyst transfers as well as single and double embryo transfers were included, but neither type nor number of embryos transferred were included in the PSM [7]. In the most recent paper from the centre, only single blastocyst transfers were included with 502 in the letrozole ± hMG group and 2280 in the HRT FET group with a significantly higher LBR (aOR 1.30 (95% CI 1.06–1.58)) and a lower MR [aOR 0.63 (95% CI 0.44–0.90)] in letrozole ± hMG compared to HRT FET [11].…”
Section: Letrozole ∗Frozen-thawed Embryo Transfer Compared To Hormone...mentioning
confidence: 99%
“…None of the studies reported a poorer live birth rate (LBR) in letrozole FET compared to HRT FET. Three papers including the only RCT reported similar live birth rate (LBR) [6,7] or ongoing pregnancy rate (OPR) [8], whereas seven retrospective studies reported improved LBR in letrozole FET compared to HRT FET [9–15].…”
Section: Letrozole ∗Frozen-thawed Embryo Transfer Compared To Hormone...mentioning
confidence: 99%
See 2 more Smart Citations
“…Using LE during in vitro fertilisation and intracytoplasmic sperm injection (IVF/ICSI) treatment has many advantages. First, LE is used to prepare the endometrium in the frozen embryo transfer (FET) cycle, and no negative effect on endometrial receptivity has yet been reported (5)(6)(7)(8). Some studies revealed that clinical pregnancy rates and live birth rates in the LE group are significantly higher, and the rate of miscarriage is significantly lower compared to those in the natural and hormone replacement cycle groups (9,10).…”
Section: Introductionmentioning
confidence: 99%